HEAVY METALS IN SERA OF PATIENTS WITH HEPATITIS B DETERMINATION AND ANALYSIS - Wahran M. Saod; Tahseen .A. Zaidan; Abdul Wahab .A. Alfaluji (Basrah Journal of Veterinary Research)
Chronic Hepatitis B is a major global health problem worldwide, However, twoBillion People could be infected with this disease Worldwide. Living organismsrequire varying amounts of heavy metals. Such as manganese(Mn), cobalt(Co) andzinc(Zn). Some heavy metals have bio-importance, but the bio toxic effects of manyof them in human biochemistry are of great concern. Heavy metals are essentialmicronutrients involved in many metabolic processes. One hundred sixty patientsamples and thirty healthy individuals were investigated in this study. All patientsincluded in this research are tested positive for the HBSAg test and their specimenswere examined by profile test which includes (HBS Ab, HBe Ag, HBe Ab, HBc Ab,(IgM-IgG), HCV and HIV) and also viral load (HBV PCR) with unit (copies/ml)were carried to test the patients sera. Manganese, chromium, cobalt, and nickel havelevels were determined by using inductively Coupled plasma- Mass spectrometry(ICP-MS). Results show a significant increase in the concentration of manganese,chromium, cobalt, and nickel in serum of patients with chronic hepatitis B compared to healthy individuals. We conclude that hepatitis B may affect the level of studiedelements in patients infected with HBV.